2006
DOI: 10.1089/acm.2006.12.237
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Acupuncture Study: The Nationwide, Randomized, Controlled, German Acupuncture Trials on Migraine and Tension-Type Headache

Abstract: The GERAC study design allowed acupuncture to be tested in a naturalistic environment. The rigorous study design and the large number of physician investigators guaranteed a high external validity for the results. The results will help determine the significance of Chinese acupuncture in the context of Western medicine for the treatment of MIG and TTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…The exact mode of acupuncture is published elsewhere [12]. In brief, verum and sham points were selected from prescribed lists.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mode of acupuncture is published elsewhere [12]. In brief, verum and sham points were selected from prescribed lists.…”
Section: Interventionsmentioning
confidence: 99%
“…Needles were inserted superficially (1-3 mm) and were not stimulated, so as to avoid De Qi in the sham group. The number (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and type of needles (sterile, singleuse needles, coated, 0.25-0.30 mm thick, 25-40 mm long), and number (10)(11)(12)(13)(14)(15), length (30 min) and frequency (2/week) of treatment sessions were the same in each group. Investigators were instructed to treat patients in each group identically in all ways other than the placement of needles.…”
Section: Interventionsmentioning
confidence: 99%
“…There is evidence that acupuncture is at least as effective as, or possibly more effective than, prophylactic drug treatment and has fewer adverse effects. 1,2 Additionally, acupuncture is a costeffective treatment option among patients with primary headache according to international cost-effectiveness threshold values. 3 However, its mode of action remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, external validity has increasingly become an issue of concern and has been raised by several acupuncture researchers. [19][20][21][22][23] Miao 23 conducted a systematic review to determine the external validity of the RCTs of acupuncture for low back pain and found major problems in the external validity of all cases. Ahmad et al 15 conducted a review and reported inadequate reporting data related to external validity specifi cally from RCTs assessing pharmacological and non-pharmacological treatments for hip and knee osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%